2021
DOI: 10.1007/s40843-021-1666-6
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-enhanced electro-thermal conversion performance

Abstract: Synergistically regulating carrier and phonon transport on the nanoscale is extremely difficult for all thermoelectric (TE) materials without cage structures. Herein BaFe 12 O 19 /Bi 2 Te 2.5 Se 0.5 thermoelectromagnetic nanocomposites are designed and synthesized as a benchmarking example to simultaneously tailor the transport properties on the nanoscale. A magneto-trapped carrier effect induced by BaFe 12 O 19 hard-magnetic nanoparticles (NPs) is discovered, which can lower the carrier concentration of n-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 39 publications
4
25
0
Order By: Relevance
“…Similar case has been found in other magnetic nanocomposites. [28][29][30][31][32][33]37 The rough interfaces and boundaries induced by Fe nanoparticles are favorable for the enhancement of phonon scattering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar case has been found in other magnetic nanocomposites. [28][29][30][31][32][33]37 The rough interfaces and boundaries induced by Fe nanoparticles are favorable for the enhancement of phonon scattering.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the ferromagnetic Fe nanoparticles form a built-in magnetic field in Ti 0.75 NiSb, which affects the carriers involved in the transport, as shown in Figure 4e. Spherical Fe nanoparticles with radius r x can generate a magnetic field of intensity B for carriers at a distance l from the spherical surface, which can be expressed as follows 29 = + B Jr l r 2 3( )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] Unfortunately, such a strategy shows little effect on the conventional TE semiconductors. [ 14,15 ] Recently, it was reported that the magnetism incorporated into various bulk TE materials can significantly enhance the electrical and thermal transport properties due to the induced thermo‐electro‐magnetic coupling effects such as electron repository effect, [ 16 ] carrier multiple scattering effect, [ 17 ] superparamagnetism‐enhanced Seebeck effect, [ 18–20 ] magneto‐trapped carrier effect, [ 21 ] magnetoresistance‐enhanced TE effect, [ 22 ] magnetic‐field‐enhanced TE effect, [ 12,13 ] and (para)magnon‐drag Seebeck effect. [ 23 ] These coupling effects induced by magnetic nanoparticles provide unconventional pathways to simultaneously regulate electrical and thermal transport properties on the same scale for all TE materials regardless of the crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric (TE) films are key materials in developing emergent applications such as wearable TE power generation, biaxial thermal management, and full solid-state refrigeration. To maximize the electro-thermal conversion and reachability, the TE films should simultaneously possess excellent TE performance magneto-trapped carrier effect, [21] magnetoresistance-enhanced TE effect, [22] magnetic-field-enhanced TE effect, [12,13] and (para) magnon-drag Seebeck effect. [23] These coupling effects induced by magnetic nanoparticles provide unconventional pathways to simultaneously regulate electrical and thermal transport properties on the same scale for all TE materials regardless of the crystal structure.…”
Section: Introductionmentioning
confidence: 99%